APPLICATION OF SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUAL (SAVI) LEARNING MODELS ON SOCIAL STUDIES LEARNING OUTCOMES FOR CLASS V STUDENTS - Nopitasari, Ade Elvina; Egok, Asep Sukenda; Yuneti, Armi (Widyagogik, 2022)
The background in this study is the low social studies learning outcomes of class V students. The learning model used to improve students' social studies learning outcomes is using the SAVI learning model. This study aims to determine the social studies learning outcomes of fifth grade students after the SAVI learning model was applied. The research method used is the one group pre-test-post-test method. The data of this study were collected through the pre-test and post-test scores for social studies learning outcomes with a total of 28 students, after being treated using the SAVI model, the students' initial abilities before being given treatment (pre-test) obtained an average value of 48,40 while after being given treatment (post-test) the average score of students was 78,94. This can be seen from the results of data processing using the Z test with a confidence level of 5% (α = 0.05). Seems like  of 6.01 and  of 1,64. This means rejected and  accepted. Thus, the hypothesis proposed in this study can be accepted as true, that the application of the SAVI learning model to the Social Studies learning outcomes of Class V students is significantly complete.